Pengaruh Penerapan Sapta Pesona terhadap Kepuasan Pengunjung di Objek Wisata Pantai Padang - Mulya, Salsya Alda; Neswardi, Sepri; Haries, Alfatah (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
This research aims to find out how Sapta Pesona influences visitor satisfaction at the Padang Beach tourist attraction. The population in this study were visitors to the Padang Beach tourist attraction with a sample size of 100 respondents. The data collection method used was by distributing questionnaires online via Google Form. Data were analyzed using validity, reliability and classical assumption tests (linearity and normality). The data analysis method used is Simple Linear Regression Analysis, t test and coefficient of determination using SPSS version 21. The results of the research show that there is an influence of Sapta Pesona on visitor satisfaction at the Padang Beach tourist attraction. Based on the T test, it is known that Tcount>Ttable (15.866>1.661). The determination test shows that Sapta Pesona has an influence of 72% on visitor satisfaction visiting Pantai Padang and the remaining 28% is influenced by other variables that have not been examined in this research.